Bmcas‐1 plays an important role in response against BmNPV infection in vitro. Issue 3 (5th May 2021) - Wang, Xin; Zhao, Zi‐qin; Huang, Xin‐ming; Ding, Xin‐yi; Zhao, Chun‐xiao; Li, Mu‐wang; Wu, Yang‐chun; Liu, Qiu‐ning; Wang, Xue‐yang
Abstract: Apoptosis, as one kind of innate immune system, is involved in host response against pathogens innovation. Caspases play a vital role in the execution stage of host cell apoptosis. It has been reported that Bmcaspase‐1 (Bmcas‐1) has a close relationship with Bombyx mori nucleopolyhedrovirus (BmNPV) infection for its differentially expressed patterns after viral infection. However, its underlying response mechanism is still unclear. The significant differential expression of Bmcas‐1 in different tissues of differentially resistant strains revealed its vital role in BmNPV infection. To further validate its role in BmNPV infection, budded virus (BV)‐eGFP was analyzed after knockdown and overexpression of Bmcas‐1 by small interfering RNA and the pIZT‐mCherry vector, respectively. The reproduction of BV‐eGFP obviously increased at 72 h after knockdown of Bmcas‐1, and decreased after overexpression in BmN cells. Moreover, the conserved functional domain of Cas‐1 among different species and the closed evolutionary relationship of Cas‐1 in Lepidoptera hinted that Bmcas‐1 might be associated with apoptosis, and this was also validated by the apoptosis inducer, Silvestrol, and the inhibitor, Z‐DEVD‐FMK. Therefore, Bmcas‐1 plays an essential antiviral role by activating apoptosis, and this result lays a fundament for clarifying the molecular mechanism of silkworm in response against BmNPV infection and breeding of resistant strains. Abstract : Once budded viruses enter into host cell, BmCytc releases into the cytoplasm for the change of mitochondrial cell membrane. The released BmCytc activates BmApaf‐1, BmNc, and BmCas‐1. The activated BmCas‐1 regulates the process of apoptosis in response to virus replication. Research Highlights: Knockdown of Bmcas‐1 could benefit BV‐eGFP infection in vitro. Bmcas‐1 plays an important role in anti‐BmNPV infection. The antiviral effect of Bmcas‐1 were related to apoptosis.